A Comparative Study of Five Target Volume Definitions for Radiotherapy in Glioblastoma Multiforme - Kamuran Ibis; Kubra Ozkaya Toraman; Canan Koksal Akbas; Ozlem Guler Guniken; Korhan Kokce; Sezi Ceren Gunay; Rasim Meral; Musa Altun (Medicina, 2025)
Background and Objectives: This study aimed to compare target volumes and organ-at-risk (OAR) doses using five different volume definitions in radiotherapy (RT) planning of patients with glioblastoma multiforme (GBM). Materials and Methods: Rigid image fusion was performed using simulation computed tomography and postoperative magnetic resonance imaging scans of 20 patients with GBM. Volumetric modulated arc therapy (VMAT) plans were generated according to three two-phase protocols—American Brain Tumor Consortium (ABTC), North Central Cancer Treatment Group/Alliance (NCCTG/Alliance), and Radiation Therapy Oncology Group/NRG (RTOG/NRG)—and two single-phase protocols—European Organisation for Research and Treatment of Cancer (EORTC) and European Society for Radiotherapy and Oncology–European Association of Neuro-Oncology (ESTRO/EANO)—each delivering a total dose of 60 Gy. OARs and dose constraints were evaluated. Statistical analysis was performed using the paired sample t-test. Results: The ESTRO/EANO volume had the smallest median PTV overall (p < 0.001). The lowest brain-PTV Dmean in the initial phase was observed in the ABTC group, followed closely by ESTRO/EANO (p < 0.001). Among boost volumes, the ABTC volume was the smallest, and the median brain-PTV Dmean was lowest in the ESTRO/EANO volume. ESTRO/EANO provided the lowest doses for contralateral and ipsilateral cochlea Dmean, brainstem D1cc, and contralateral lens Dmax. Notably, both EORTC and ESTRO/EANO plans maintained OAR doses within acceptable constraints, with ESTRO/EANO achieving the most consistently minimised exposure. Conclusions: Reduced irradiated brain volume, acceptable OAR preservation and practical applicability, the use of ESTRO-EANO and EORTC target volumes in radiotherapy of glioblastoma multiforme may provide dosimetric advantages that require further validation in clinical outcome studies.